Polyimide nanocomposites in ternary structure: A novel simultaneous neutron and gamma-ray shielding material - Baykara, Oktay; Irim, Serife G.; Wis, Abdulmounem A.; Keskin, Mustafa A.; Ozkoc, Guralp; Avc, Ahmet; Dogru, Mahmut (Wiley, 2020)
The aim of this study is to develop a novel shielding material against both neutron and gamma rays. For this purpose, multi-functional polyimide nanocomposites with two different nanoparticles fillers, that is, h-BN and Gd2O3, was designed and fabricated through conventional melt extrusion processing techniques via laboratory batch twin-screw compounder. The morphology and structure of both fabricated nanoparticles and their nanocomposites were characterized by SEM, TEM, XRD. Moreover, the mechanical properties of nanocomposites were investigated. High energy neutron and gamma radiation shielding performance of nanocomposites having h-BN and Gd2O3 were examined in detail by means of Neutron Howitzer. The results indicated that the presence of nanoparticles in polyimide significantly influenced both the radiation shielding and mechanical properties of nanocomposites. It was found that nanocomposites could be used for high energy neutron shielding purposes in nuclear reactor system, nuclear waste disposal applications, space, and aeronautics industries.
Keywords: gamma rays; hexagonal boron nitride; nanocomposites; neutron shielding; polyimide